Phytochemical profile and antioxidative properties of Plinia trunciflora fruits: A new source of nutraceuticals. (1st March 2020) - Mannino, Giuseppe; Perrone, Anna; Campobenedetto, Cristina; Schittone, Adele; Margherita Bertea, Cinzia; Gentile, Carla
Highlights: TPC of P. trunciflora is higher than fruits listed in polyphenol top-ranking. HPLC-DAD-MS/MS identified 16 polyphenols in Plinia trunciflora fruit extracts. Anthocyanins account for more than 70% of the amount of identified polyphenol. CAA of P. trunciflora fruit is higher than those of others colourful fruits. P. trunciflora fruit extracts modulate SOD and GPx gene expression. Abstract: This study evaluated the polyphenol profile and the antioxidative properties of Plinia trunciflora (O. Berg) Kausel fruits. Folin-Ciocalteau and pH-jumping methods indicated that these berries are a major source of antioxidant polyphenols (1201.05 mg GAE/100 g FW), particularly anthocyanins. HPLC-DAD-ESI-MS/MS analysis identified cyanidine glycosides as the main components. Flavon-3-ols and hydrolysable-tannins were also found. CAA assay showed that extracts of P. trunciflora fruits prevent lipid peroxidation in HepG2 cells with higher efficacy than other colourful fruits (CAA50 935.25 mg FW/mL cell medium). Moreover, our results suggested that the observed antioxidant protection involve both redox active properties of P. trunciflora components, as measured by ABTS, DPPH and FRAP assays, and upregulation of the genes coding for the antioxidant enzymes MnSOD and GPx, as evaluated by qRT-PCR. Collectively, our data provided evidence on the potential of P. trunciflora fruit as a very rich source of natural antioxidant molecules.